Diagnostic ability of otoacoustic emission and automated auditory brainstem response in hearing screening of high-risk newborn - Chandramohan, Rema; Chandramohan, Asmita; Ramanathan, Karthik (International Journal of Contemporary Pediatrics, 2022)
Background: Early identification of hearing impairment in infants and appropriate intervention can prevent severe psychosocial, educational, and linguistic repercussions. Infants who are not identified before 6 months of age have delays in speech and language development. Methods: This was a prospective cohort study OAE and AABR were administered to high-risk neonates discharged from NICU and the diagnostic ability to pick up hearing loss was assessed by trained audiologist. Statistical analysis was interpreted by McNemar paired Chi-square test (χ2) test. Factors which correlated with deafness were interpreted by Pearson chi-square (χ2) test. Results: Among 144 babies screened, 26 failed OAE while 6 failed AABR. Referral rate was 18.1% with OAE and 4.2% with AABR. All 6 babies failed with 40db and 90 db screening. Mean duration of NICU stay had a positive correlation with AABR positivity. Babies with higher duration of NICU stay had greater probability of hearing loss. Age and gender had no significant correlation with hearing loss. Sensitivity of OAE as 16.7 % and the specificity was 81.9 %. Positive likelihood ratio with OAE was.923. Negative likelihood ratio with OAE was 1.02. One neonate out of 6 with jaundice had profound hearing loss. Conclusions: It was concluded that in high-risk neonates the diagnostic value of DPOAE for identification of hearing loss, when used alone, was limited since OAE has higher referral rate and lower specificity compared to AABR. Babies with higher duration of NICU stay had greater probability of hearing loss.